EDUKASI PENERAPAN PROTOKOL KESEHATAN DI TPA AN-NUR, DUKUH GADING, NGARGOSARI, AMPEL, BOYOLALI - SITI NURHANA; UNNA RIA SAFITRI; DONNA SETIAWATI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
TPA or TPQ stands for an educational park. The Koran is a community institution that provides non-formal Islamic education which aims to increase knowledge of Islamic religious knowledge, such as reading the Koran, how to read the Koran properly and correctly according to science Tajweed, memorizing prayers that are applied in our daily lives, doing prayer 5 times. As well as helping children's growth and development in order to have life guidelines and readiness to enter further education. Tpa which is usually attended by children of kindergarten, SD / MI ( Elementary school) , Junior High School (SMP) and Senior High School(SMA). TPA education is not mandatory, however, to form children's character, they must attend TPA. So that children can have a good personality and can be followed by other children. It takes an understanding of the contents of the Al-Qur'an to practice Islamic religious education that is obtained in daily life seriously. Practicing the teachings that exist in Islam and stay away from its prohibitions